Lysimachia daqiaoensis (Primulaceae), a new cave species from Guangdong, China - Huang, Rui-Zhou; Liao, Miao; Han, Wei; Yang, Yuan-Zhi; Zhou, Ming-Yi; Feng, Han-Hua; Tang, Guang-Da (Phytotaxa, 2020)
Lysimachia daqiaoensis, a new species of Primulaceae endemic to a limestone cave in northern Guangdong, China, is described and illustrated. It is most similar to L. rupestris in having rosette leaves and being glabrous all over the plant, but it differs from the latter by absence (vs. presence) of stolon, flowers in racemose and solitary (vs. solitary only), and anthers shorter and dorsifixed with opening by lateral slits (vs. longer and basifixed with opening by apical pores).